Electrochemical Polymerization Provides a Function‐Integrated System for Water Oxidation. (1st February 2021) - Iwami, Hikaru; Okamura, Masaya; Kondo, Mio; Masaoka, Shigeyuki
Abstract: Water oxidation is a key reaction in natural and artificial photosynthesis. In nature, the reaction is efficiently catalyzed by a metal‐complex‐based catalyst surrounded by hole‐transporting amino acid residues. However, in artificial systems, there is no example of a water oxidation system that has a catalytic center surrounded by hole transporters. Herein, we present a facile strategy to integrate catalytic centers and hole transporters in one system. Electrochemical polymerization of a metal‐complex‐based precursor afforded a polymer‐based material (Poly‐1 ). Poly‐1 exhibited excellent hole‐transporting ability and catalyzed water oxidation with high performance. It was also revealed that the catalytic activity was almost completely suppressed in the absence of the hole‐transporting moieties. The present study provides a novel strategy for constructing efficient molecule‐based systems for water oxidation. Abstract : Four‐electron oxidation of water with a function‐integrated polymer is reported. Electrochemical polymerization provided a material with molecule‐based active sites and hole‐transporting moieties (see picture). Electrochemical impedance analysis revealed that the hole‐transporting polymer reduced charge‐transfer resistance. The material catalyzed electrochemical water oxidation with high faradaic efficiency and a low overpotential.